Endowing university spin-offs pre-formation: Entrepreneurial capabilities for scientist-entrepreneurs (2020)
University spin-offs are important mechanisms for creating and capturing value from scientific inventions. Academic scientists are uniquely positioned to shape such opportunities long before the university spin-off is founded. To better understand how science-based university spin-offs can be endowed for success, the pre-formation stage of 30 ventures co-founded over a 40 year period by a star-scientist-entrepreneur is analysed by matching his 363 co-invented US patents granted to 1476 co-authored publications and these 30 ventures. Employing the extended case method, including the analysis of extensive archival data, iterative interviews, and this unique, longitudinal, multi-level dataset, existing dynamic capabilities theory is confronted and extended with evidence as to how a star-scientist-entrepreneur senses and shapes and seizes opportunities to endow university spin-offs pre-formation. A process model is developed depicting four pre-formation entrepreneurial capabilities with which these science-based university spin-offs are endowed for success. Recommendations are made for scientist-entrepreneurs, investors, university leadership, and for innovation policymakers.